Money master: a gamified apps for financial literacy / Mior Muhammad Hafidz M. Aminuddin, Nurul Hidayah Mat Zain and Azlan Abdul Aziz - M. Aminuddin, Mior Muhammad Hafidz; Mat Zain, Nurul Hidayah; Abdul Aziz, Azlan (College of Computing, Informatics, and Mathematics, 2024)
Learning about money is important, but it can be kind of hard for many people. This project, called MoneyMaster, tries to solve this problem by making a fun app to teach you about money in a game- like way. According to the study, most of the adult population lack the knowledge in financial literacy and lack of enjoyment causes them to carelessly keep track of their finances. MoneyMaster aims to change that. This project intends to create an application for android mobile phone that helps people understand money better and makes it fun to learn. The goal is to design a game-like interface about financial literacy, to develop a gamified application for financial literacy and to evaluate if this project provides an enjoyable approach and enjoyable experience in the gamified application for financial literacy. This project uses Agile Methodology as it is the most suitable to develop this application successfully. Three elements from MDA Framework are implemented in this project: mechanics, dynamics, and aesthetics. After making the app, the app is evaluated to see if people enjoy it and if it really helps them understand money better through questionnaire based on the Scale of EGameFlow. The results shows that the project scores high percentage of enjoyment, which is 84.40%. The finding suggests that the application succeeded in satisfying the third objective of MoneyMaster. Future work can be applied to the project by providing the option of multilanguage to the user.